Differences in Mandibular Cortex Thickness in Pre-Menopause and Menopause Patients (Cross-Sectional Study at RSIGM Sultan Agung Semarang) - Hapsari, Nikita Muthmainna; Yusuf, Moh; Putranto, R. Rama (Universitas Muhammadiyah Yogyakarta, 2026)
Radiographic examination in dentistry plays a role in determining a diagnosis in the oral cavity. Panoramic radiography is useful for detecting abnormalities in the hard tissues of teeth. Changes in the mandibular cortex are influenced by various factors, one of which is estrogen. Menopausal women, specifically, experience a decrease in estrogen levels, leading to changes in the thickness of the mandibular cortex. To determine the difference in thickness of the mandibular cortex in pre-menopausal and menopausal patients (cross-sectional study at RSIGM Sultan Agung Semarang). The research method is analytical. The research group was divided into two groups, including pre-menopausal and menopausal patients. Images would be analyzed using the panoramic mandibular index (PMI) method with ImageJ Version 1.53t. Group data was calibrated by researchers using Intraclass Correlation Coefficients (ICC) with three observers. Afterward, the radiographic analysis results for each sample would be processed in SPSS. The ICC test results scored 0.779 in pre-menopausal patients, and 0.794 in menopausal patients (k>0.75), which is in good agreement with the data. The results of the independent t-test revealed a significant difference in mandibular cortex thickness of 0.006 in the right region and 0.007 in the left region (p<0.05) in pre-menopausal and menopausal patients. There was a difference in mandibular cortical bone thickness between pre-menopausal and menopausal patients based on the panoramic mandibular index (PMI). This finding suggests that panoramic radiography, particularly PMI measurements, may serve as a supportive screening tool to detect reduced bone density in menopausal patients, thereby aiding early identification of individuals at risk for osteoporosis.